Association between history of stroke and sleep disturbances in U.S. adults - Wendemi Sawadogo; Tilahun Adera; Juan Lu (Taylor & Francis Group, 2022)
: Nearly one-third of U.S. adults do not get enough sleep regularly. Poor sleep quantity and quality are associated with many chronic diseases and conditions. Sleep outcomes are likely to deteriorate after a stroke and could delay recovery. In this cross-sectional analysis, we examined the association between a history of stroke and sleep disturbances. Multivariate logistic regression models were developed for each outcome accounting for the multiple-stage sampling design. After adjustment for confounders, a history of stroke was significantly associated with taking sleep medication (OR = 1.8, 95% CI: 1.1-3.0) but not with trouble staying asleep (OR = 1.3; 95% CI: 0.9-1.9) regardless of age, sex, and race. However, sex difference was observed for waking up not feeling well-rested, in which the association was significant for females (OR: 2.0, 95% CI = 1.1-3.6) and not for males (OR: 0.9; 95% CI = 0.6-1.5). Similarly, race difference was observed for trouble falling asleep, in which the association was significant for Non-Hispanic White (OR = 2.0; 95% CI: 1.3-3.0) and not for Non-Hispanic Black (OR = 0.4; 95% CI: 0.1-2.0). The association between a history of stroke and sleep disturbances varies by sex and race, indicating a significant association among females and Non-Hispanic Whites. A holistic approach to stroke rehabilitation that includes targeted sleep interventions is warranted.